Peran Sistem Manajemen Kinerja, Kompetensi Pegawai dan Promosi Jabatan dalam Meningkatkan Kinerja Pegawai - Alimudin, Arasy (Jurnal Ekonomi Modernisasi, 2017)
The purpose of research to determine the factors that affect employee performance. The study is conducted at Rumah Sakit Mata Jawa Timur. Respondents numbered 70 people other than doctors. Analytical technique used is SEM PLS that test the causal relationship between variables. The results show that the performance management system and employee competence do not affect on the performance. Performance management system and employee competence affect on promotion position. Promotion position affect the performance of employees. The finding is performance management system can not improve the performance of employees if not supported by incentives to employees. Suggestions for further research to test incentive variables as variable that mediates the relationship between performance management systems and employee performance.